Development Of Liquid Chromatographic Methods For The Determination Of Aflatoxins And Fumonisins In Food And Feeds - Al-Debi, Wijdan Shakir Khayoon (2012)
New sample preparation methods (using multifunctional clean-up column (MFC) and micro-solid phase extraction (μ-SPE) for the high performance liquid chromatography (HPLC) determination of aflatoxins (AFs) B1, B2, G1 and G2 are described. For the MFC method, the samples were first extracted using acetonitrile:water (90:10) and further purified using a single step. Optimum conditions for the extraction and chromatographic separation (using fluorescence detector (FLD)) were investigated. After the optimization, the developed method was applied for the determination of AFs in forty two animal feeds samples comprising corn (16), soya bean meal (8), mixed meal (13), sunflower, and 1 sample each of wheat, canola, palm kernel, copra meals.